Socialization and Training on Learning Outcomes and Merdeka Belajar Digital Modules with the Context of Local Wisdom at SMAN 1 Mengwi - Arjaya, Ida Bagus Ari; Surata, Sang Putu Kaler; Paraniti, Anak Agung Inten; Hermawan, I Made Surya (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2025)
Although SMAN 1 Mengwi is recognized as one of the top high schools in Badung Regency, challenges persist in the development of Learning Outcomes (CP), Learning Objectives (TP), Learning Objectives Flow (ATP), and the integration of the Merdeka Belajar Digital Module with local wisdom. A community service program addressed these gaps and enhanced teachers' knowledge and skills in these critical areas. 38 teachers from SMAN 1 Mengwi participated in this socialization and training initiative, which adopted a structured approach encompassing initial observation, program design, implementation, and evaluation, guided by the Community-Based Participatory Research (CBPR) method. The program revealed that while teachers possessed foundational knowledge of module structures and were aware of local wisdom within their subject areas, they encountered difficulties applying this understanding to preparing CP, TP, and ATP components. Pre-test and post-test assessments significantly improved teachers' comprehension and capability to prepare CP, TP, ATP, and integrate local wisdom into digital modules. Notably, teachers' understanding level regarding CP, TP, and ATP reached 87.41%, while the overall success rate of the socialization and training program participation achieved 100%. These outcomes underscore the program's effectiveness in significantly enhancing teacher competence, ultimately contributing to the advancement of educational practices at SMAN 1 Mengwi and reinforcing the integration of local genius within the framework of modern pedagogy.